1494. Vaginal pH: Associations with Neisseria gonorrhoeae, Chlamydia trachomatis, and Trichomonas vaginalis. (26th November 2018) - McLaughlin, Stephanie; Ghanem, Khalil G; Page, Kathleen; Griffiss, John Mcleod; Tuddenham, Susan
Abstract: Background: Bacterial vaginosis (BV), a low- Lactobacillus state characterized by elevated vaginal pH, has been associated with incident sexually transmitted infections (STIs). Elevated pH may also be associated with certain Lactobacillus species ( L. iners ). Increased pH may serve as a cheap, easily accessible biomarker for underlying STI, vaginal dysbiosis and risk of STI acquisition. In this study we examine the relationship between vaginal pH and infection with Neisseria gonorrhoeae (GC), Chlamydia trachomatis (CT ) and Trichomonas vaginalis (TV ). Methods: This study used data from women attending Baltimore City STI clinics from 2005 to 2016. Those with a vaginal pH determination and testing for GC, CT or TV were included. Most GC and CT testing was conducted using nucleic acid amplification tests, while TV was diagnosed via microscopy. Generalized estimating equations with a logit link were utilized to explore relationships between vaginal pH and STI, accounting for confounders and repeated within patient measures. Results: A total of 28, 333 individual women contributed 63, 032 visits. Mean age was 28.9 (SD 9.8), 4.5% were Caucasian and 91.5% were Black. 42.5% had BV via Amsel's criteria. Of 11, 577 total STI cases 2056 (17.8%) had a pH < 4.5. 22.2% of GC cases, 28.2% of CT cases, and 7.4% of TV cases had a pH <4.5. After adjustment for age, race, number of sexual partners in the past 6 months, and HIV sero-status, a pH ≥4.5 was associated an increased odds of GC (OR: 1.86 (CI 1.66–2.09)), CT (OR: 1.44 (CI 1.34–1.53)), and TV (OR: 6.50 (CI 5.98–7.16)) infection as compared with a pH of < 4.5. These relationships remained significant in subjects without symptomatic BV and when each analysis was restricted, separately, to those who reported exposure to a partner with GC, CT or nongonococcal urethritis, or TV. Conclusion: Elevated vaginal pH is associated with urogenital STI and may serve as a useful biomarker for underlying infection. This analysis was not able to assess causality, though pH remained predictive when restricted to those reporting STI exposure, perhaps suggesting that high pH increases risk of STI acquisition. Further prospective studies are required to confirm these findings and to mechanistically define relationships between vaginal pH, resident microbiota, and STI. Disclosures: All authors: No reported disclosures.